PDAM Aplikasi Registrasi Pelanggan Baru Pada PDAM Tirta Betuah Cabang Mariana Berbasis Web - Sasmita, Rianti; Hari Pertiwi, Dini; ., Fatmariani; Effendi, Hendra (Universitas Multi Data Palembang, 2024)
PDAM Tirta Betuah Mariana Branch is a local government-owned business entity engaged in the service and provision of clean water. One form of PDAM service to its customers is new customer registration. Currently, PDAM Tirta Betuah Mariana Branch still uses a manual system for new customer registration data collection. This causes the customer registration process to be less effective and efficient. The author designed a web-based new customer registration application at PDAM Tirta Betuah Mariana Branch. This application uses the Extreme Programming (XP) development method. The scope of the application includes new customer data, new connection output, and the registration process up to providing installation information to new customers. The purpose of this application is to improve employee performance and provide convenience to the community in the process of registering new customers.